Determinants of Demand for Health Care Among Sexually Transmitted Infections Patients in Kenya - Ogola, Pauline; M. Kioko, Urbanus (European Scientific Journal, ESJ, 2022)
Globally, sexually transmitted infections (STIs) have become an enormous burden leading to high mortality and morbidity. In Kenya, various policies have been formulated to address various conditions including STIs. Individuals suffering from STIs are highly encouraged to seek medical care and avoid transmitting to uninfected individuals. In Kenya, about 14% of men and 25% of women never sought treatment for STIs or advice from any healthcare service provider. Furthermore, 42% and 23% of people with sexually transmitted infections had been symptomatic for a period of one and two weeks respectively. Although numerous studies have been conducted in many countries to establish the determinants of healthcare use among people with sexually transmitted infections, there is still very little information on the determinants of healthcare use among STI patients in Kenya. The aim of this study was to determine factors influencing health care demand for STIs in Kenya. The study analyzed data from the 2014 Kenya Demographic Household Survey (KDHS). Descriptive statistics and binary probit regression analyses were done to explore factors influencing the use of health services among STI patients in Kenya. The findings revealed that the age of the patient, sex, marital status, education levels, wealth quintiles, employment status, residence, and sex partners were statistically significant determinants of the utilization of healthcare services among STI patients in Kenya.